2018
DOI: 10.1177/0192513x18821395
|View full text |Cite
|
Sign up to set email alerts
|

Postdivorce Coparenting Relationships and Parent–Youth Relationships: Are Repartnership and Parent–Youth Contact Moderators?

Abstract: Using data from 392 divorced mothers and fathers, living in the United States, with a child between 10 and 18 years old, we first identified three types of postdivorce coparenting relationships ( cooperative, moderately engaged, and conflictual and disengaged) based on coparenting communication, cooperation, and conflict. We then tested if three aspects of parent–youth relationships differed between those groups. Parental warmth and support, parental knowledge, and inconsistent discipline did not differ based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 60 publications
3
26
0
3
Order By: Relevance
“…We suggest that family therapists should shift the focus from solving co‐parental relationship problems to help each parent in a prolonged conflict to buffer the risk and promote resilience in their child. This approach is in line with research that indicates that parent–youth relationships might not be affected by divorced parents engaging in conflictual co‐parenting and that recommending alternative forms of co‐parenting (e.g., parallel) could better meet the needs of parents and youth (Beckmeyer et al, 2019). Kelly (2007) argues that children appear to thrive with parents who engage in conflict‐free parallel parenting if they have adequate parenting in both homes and well‐articulated parenting agreements.…”
Section: Discussionsupporting
confidence: 72%
“…We suggest that family therapists should shift the focus from solving co‐parental relationship problems to help each parent in a prolonged conflict to buffer the risk and promote resilience in their child. This approach is in line with research that indicates that parent–youth relationships might not be affected by divorced parents engaging in conflictual co‐parenting and that recommending alternative forms of co‐parenting (e.g., parallel) could better meet the needs of parents and youth (Beckmeyer et al, 2019). Kelly (2007) argues that children appear to thrive with parents who engage in conflict‐free parallel parenting if they have adequate parenting in both homes and well‐articulated parenting agreements.…”
Section: Discussionsupporting
confidence: 72%
“…It is a worldwide phenomenon that in the majority of families, children stay with their mothers after parental break up and suffer from less contact or even no contact and involvement with their fathers (e.g., Holt, 2016; Kalmijn, 2015; Köppen, Kreyenfeld, & Trappe, 2018). However, it has been shown that the involvement of fathers after family dissolution has positive effects on children’s well‐being in many respects (e.g., Adamsons & Johnson, 2013; Beckmeyer, Stafford Markham, & Troilo, 2019; Kalmijn, 2016; Poortman, 2018). Thus, it can be expected that there is an association between children’s well‐being and the physical custody arrangement in nonintact families that formalizes the time that children spend with their parents.…”
mentioning
confidence: 99%
“…The fact that several studies have found similar postdivorce coparenting patterns based on data collected between 1984 and 2016 among divorced and separated mothers and fathers with children between 3 and 19 years old speaks for the reliability and generalizability of its findings. Nevertheless, researchers have noted that children may perceive coparenting relationships differently than parents (e.g., Beckmeyer et al, 2019). Co-parents may not agree on how they assess their coparental relationship, and parents may overestimate their own coparenting skills.…”
Section: Postdivorce Coparenting Patterns and Adolescent Adjustmentmentioning
confidence: 99%